LATO-LATO GAME AS A PREVENTIVE EFFORT NOMOPOBHIA - Uswatun Hasanah; Sitti Khotijah; Fayruzah El-Faradis (Media Inovasi Pendidikan dan Publikasi, 2023)
Handphone is one of tool that required by huge number of Indonesian citizens. Both in cities, or villages, from children, teenagers, adults required its, they use a lot of handphone and internet in their lives, for various interests in their lives, both things that are really useful for them, or just playing around, so this tools absolutely have positive and negative effect. For those who can use it for positive things, the tools can help them and facilitate their various needs, For people who couldn't use it in positive ways, they only playing, stalking and watching the nonsense things that caused the nomophobia, the insecurity when apart from their handphones or mobiles, means, wherever and whenever they go, their mobiles is in, not based on their needs, but it’s their self-addictive. Nowadays lato-lato as traditional game is very popular in Indonesia, that caused happiness in children's face. This research aims to know how lato-lato game as preventive effort of nomophobia, and what are obstacles faced by parents to prevent nomophobia, to children. This research is qualitative descriptive, data collection technique by interview and observation, and to check the validity of data used triangulation by comparing interview result and observations. The result shown that the citizens is helped by this lato-lato game to prevent their children from handphone addict, but sometimes this game also make the children lazy to do their responsibilities.